2020
DOI: 10.1080/03639045.2019.1706552
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of buprenorphine in opioid use disorder treatment: a review of pharmacodynamic and efficacy data

Abstract: Context: There is currently no consensus regarding optimal dose or dose-range of buprenorphine (BUP) for treatment of opioid use disorder (OUD). Objective: To elucidate the relationship between BUP dose and opioid receptor blockade, retention in treatment and illicit opioid drug use. Methods: Systematic review of the scientific literature through searches in the databases MEDLINE and PubMed. Results: The review of the opioid receptor blockade studies did not find evidence that a daily sublingual (SL) BUP table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…However, the overall absence of association of BUP-NX dose with retention is in line with a relatively recent review that did not find associations between higher doses and retention in treatment. 27 This may partly stem from the flexible dosing approach in the present trial and the possibility that participants with higher risk of negative outcomes were more likely to require higher buprenorphine dosage. Although BUP is a partial µ-opioid receptor agonist, its most potent effects seem to occur in doses ranging from 4 to 16 mg/day of BUP, conferring a potential dose-ceiling effect.…”
Section: Discussionmentioning
confidence: 97%
“…However, the overall absence of association of BUP-NX dose with retention is in line with a relatively recent review that did not find associations between higher doses and retention in treatment. 27 This may partly stem from the flexible dosing approach in the present trial and the possibility that participants with higher risk of negative outcomes were more likely to require higher buprenorphine dosage. Although BUP is a partial µ-opioid receptor agonist, its most potent effects seem to occur in doses ranging from 4 to 16 mg/day of BUP, conferring a potential dose-ceiling effect.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, results from a secondary analysis of adults with OUD receiving BUP and methadone (Hser et al 2014 ) support that BUP daily doses over 16 mg and methadone daily doses above 60 mg were significantly associated with higher retention in treatment over 24 weeks (Hser et al 2014 ). Nevertheless, a recent systematic review found no conclusive evidence on the association of BUP daily dose with treatment outcomes (Hjelmström et al 2020 ). The systematic review concluded adjusting BUP maintenance dose according to clinical response, i.e., opioid use, may be optimal compared to dose adjustment in response to signs and symptoms of withdrawal and craving (Hjelmström et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent systematic review found no conclusive evidence on the association of BUP daily dose with treatment outcomes (Hjelmström et al 2020 ). The systematic review concluded adjusting BUP maintenance dose according to clinical response, i.e., opioid use, may be optimal compared to dose adjustment in response to signs and symptoms of withdrawal and craving (Hjelmström et al 2020 ). This may suggest a difference in the BUP doses required to suppress craving compared to doses required to suppress opioid use over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is extensive research in the area of precision medicine to improve individualized medication-assisted treatment of OUD [53], to date research has failed to provide clear evidence for certain patients characteristics or genomic profiles to predict response to methadone or buprenorphine treatment. In addition, the optimal buprenorphine dose (over 8 mg sublingual) to ensure opioid receptor blockade has also still to be defined [65]. Despite advances in the pharmacological management of OUD, entry into, induction of, and adherence to treatment remain important tasks [66].…”
Section: Discussionmentioning
confidence: 99%